AgNO3 as nitrogen source for rhodium(iii)-catalyzed synthesis of 2-aryl-2H-benzotriazoles from azobenzenes. Issue 61 (11th July 2016) - Li, Jixing; Zhou, Hui; Zhang, Jinlong; Yang, Huameng; Jiang, Gaoxi
Abstract : A new approach has been established for Rh(iii )-catalyzed direct aza oxidative cyclization of non-prefunctionalized azobenzenes to provide 2-aryl-2 H -benzotriazoles in good yields. Abstract : A new approach has been established for Rh(iii )-catalyzed direct aza oxidative cyclization of non-prefunctionalized azobenzenes to provide 2-aryl-2 H -benzotriazoles in good yields, in which AgNO3 instead of conventional azide reagents for the first time functions as the nitrogen source for the nitrogenation reaction. Preliminary mechanistic studies suggest that the Rh(iii )-catalyst could account for the nitration reaction, and subsequently cationic silver species might both play a vital role in the fission of the nitrogen–oxygen bonds in nitro groups and promote aza oxidative cyclization.